Alarm Fatigue Among Healthcare Workers Working in Intensive Care Unit: A Cross-sectional Study - Pant, Chiranjibi; Shrestha, Bipin Kumar; K.C, Rajesh (Medical Journal of Shree Birendra Hospital, 2025)
Introduction: Alarm fatigue, characterized by desensitization to alarms, is a prevalent issue among healthcare workers (HCWs), particularly those in intensive care units (ICUs). The constant exposure to device-related alarms both genuine and false can significantly impact human health and behavior. In this study, the consequences of alarm fatigue delve into and its effects on HCWs. Methods: This descriptive analytic study was conducted in different ICUs of Shree Birendra Hospital, Kathmandu, Nepal from 1 February, 2024 to 1 March, 2024. Data was collected by using standard Charité Alarm Fatigue Questionnaire (CAFQ) Likert scale based response was collected from all the participants and the data were analyzed. Results: Total 87 HCWs working in ICU had participated in this study. 57 (65.5%) participants were working in ICUs for more than one year. 76 % participants were working for 12 hours per day. 55 (63%) knew about alarm fatigue, three (3.4%) had never heard about alarm fatigue and remaining 20 (33%) had minimum prior knowledge. In this study, it was found that 29 (33.7%) ICU working staffs were having alarm fatigue with, score range (18 - 27). In 50%, alarm made them confused, triggered physical symptoms in 36 (41%), reduced concentration in 34 (39%), and interruption workflow in 27 (31%) of HCWs. Conclusions: Alarm in ICUs poses a significant fatiguein HCWs (33.7%). Balancing patient safety with minimizing alarm burden requires a multifaceted approach. By addressing alarm management systematically, the consequences of alarm fatigue can mitigate and enhance patient care.